Effect of rhizobium phaseoli inoculation and phosphorus application on nodulation, growth and yield components of two drybean (phaseolus vulgaris) cultivars - Ndlovu, Tshepo John (My University, 2015)
Low yields in dry bean are often reported to be associated with lack of inoculation of seeds prior to planting. This also results in little fixed nitrogen contributed by the crop. Soil phosphorus (P) is another important yield limiting factor in most of the dry bean producing regions. Two field experiments were conducted to investigate the response of dry bean cultivars to inoculation and phosphorus application under dryland farming conditions during 2011/2012 and 2012/2013 growing seasons at the Syferkuil farm of University of Limpopo. The experiments were carried out as a split split-plot arrangement in randomized complete block design with four replications. Main plot factor comprised two dry bean cultivars viz, red speckled bean and small white haricot. Rhizobium phaseoli inoculation levels (inoculated and uninoculated) were assigned in the sub-plot whilst the sub-sub plot was applied with three phosphorus rates at 0, 45 and 90 kg P kg/ha. Growth parameters, phenological characteristics and yield data were collected during the course of the experiments. The results of the two experiments showed that there was no interactive effect of treatments on growth and yield parameters. However, there was a significant interactive effect of cultivar and inoculation on phenological characteristics in both growing seasons. Main effects of cultivar and inoculation significantly affected most of the parameters measured. Inoculated red speckled bean produced tallest plants which reached 50% flowering and maturity earlier than the small white haricot variety. In both growing seasons grain yield was significantly different between the two cultivars (P ≤ 0.01). The red speckled bean produced higher grain yield of 1657 kg ha-1 and 2547 kg ha-1 in 2011/2012 and 2012/2013, respectively. In contrast, the small white haricot bean achieved grain yield of 1396 kg/ha and 1797 kg/ha in the respective seasons. Grain yield was significantly increased by approximately 16.15% and 27.50% with Rhizobium inoculation in the respective seasons. Phosphorus application at varying rates did not have a significant influence on all parameters measured the experiment in both 2011/2012 and 2012/2013 seasons.
Thesis (M.Sc. Agriculture (Agronomy)) -- University of Limpopo, 2015
Keywords: Dry bean; Phosphorus fertilizers; Rhizobium; Rhizobium.; Phosphatic fertilizers.; Field crops -- Varieties.